Product Innovation as a Competitive Advantage for Emerging Multinationals: The Case of the Judge Revolver in The USA - Machado, Marcelo André; Azambuja, André Volkman (Internext, 2018)
This paper aimed to evaluate the product innovation as a resource in the internationalization process of an emerging multinational (EMN), the Brazilian company Taurus in the North American market. Through the lenses of the Resource Based View (RBV), we discuss the role of product innovation, the case of The Judge revolver, as a resource for competitive advantage in the internationalization process of an EMN. In-depth interviews were conducted with managers involved in the development and introduction of the product into the USA market, as well as document analysis and direct observation. The results indicated that an innovative product can be vital for an emerging multinational entering a developed market. Other result points out that an innovative product of an EMN is capable of provoking competitive responses in developed markets where the product was introduced.